Site of Deportation, Site of Memory : The Amsterdam Hollandsche Schouwburg and the Holocaust - Duindam, David; Berg, Hetty; Vree, Frank van (Book collections on Project MUSE., 2019)
The Hollandsche Schouwburg is a former theatre in Amsterdam where, during the Nazi occupation of the Netherlands, tens of thousands of Jews were assembled before being deported to transit and concentration camps. Before the war, the theatre had been an example of Jewish integration in the Netherlands, and after the war it became a memorial for the Jewish victims of Nazi persecution. This book is the first international publication to address all the historical aspects of the site, putting it in a broader European and historical context.